Optimization of Extraction Process for Total Flavonoids of Lycium Barbarum by Response Surface Methodology. Issue 1 (March 2021) - Na, An; Lihui, Wang
Abstract: To optimize the Soxhlet extraction technology for total flavonoids of lycium barbarum by response surface methodology (RSM). Methods: On the base of single factor experiments, liquid to solid ratio, particle size and extraction time were selected as the main factors, with the extraction capacity as the response values, RSM was used to optimize the Soxhlet extraction process. Results: Optimal parameters were as follows: the particle size was 70 meshes. liquid to solid ratio was 17.59 ml/g, extraction time was 2.47hours. Under these conditions, the extraction capacity was 14.57 mg/g on average, and the experimental values agreed with the predicted values. Conclusion: This optimized extraction technology for total flavonoids of lycium barbarum is stable, feasible and reasonable, and with high accuracy, which could could guide the applications of production.